If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 2y = 6 Solving 8 + 2y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 2y = 6 + -8 Combine like terms: 8 + -8 = 0 0 + 2y = 6 + -8 2y = 6 + -8 Combine like terms: 6 + -8 = -2 2y = -2 Divide each side by '2'. y = -1 Simplifying y = -1
| z/7-5/6 | | -12x^3+20x^2= | | 1/125=5^-3 | | k/7=k/9-2 | | s=11.25 | | -12x^2+5x=-2 | | Y=2+2y-4 | | (5/6x-1/4x+4)=7/10x | | 1s=11.25 | | z/5+4=8/5 | | -8^(1/3) | | 3s=33.75 | | 3x^3+48x=24x^2 | | 3x+2/4 | | 8^(-4/3) | | Z^2-13z+24+12=0 | | -2(2x+5)=(-42) | | 3+16n-1=8n+52-2n | | 2x+20=x+6 | | 169^(-1/2) | | (2x-3)(x^5-4x+7)=0 | | 9x^2-18x=-14 | | 19w/5/8/5 | | 3s-3.75=30+3.75 | | (1/4+z)(1/4+z)=0 | | a/a+3-a-4/a | | 8y+11y=95 | | 6x+16=2x+28 | | 2136-212= | | z/11=-17 | | 7a+5=5a+12 | | x^2+y^2+6x-2y+10=36 |